Safety, Feasibility, and Effectiveness of Weighted Blankets in the Care of Infants With Neonatal Abstinence Syndrome: A Crossover Randomized Controlled Trial. (October 2020) - Summe, Virginia; Baker, Rachel B.; Eichel, Margaret M.
Abstract : Background: Nurses are caring for increasing numbers of infants diagnosed with neonatal abstinence syndrome (NAS). The recommended initial line of treatment to alleviate NAS symptoms includes nonpharmacologic interventions; however, there is little rigorous evidence on the effectiveness of nonpharmacologic interventions. Purpose: The purpose of this study was to assess the safety, feasibility, and effectiveness of weighted blankets in the care of NAS infants. Methods: This pilot study was a crossover randomized nonblinded controlled trial conducted at a level III neonatal intensive care unit. Infants' care included 30-minute sessions utilizing either a nonweighted or weighted blanket, with infants serving as their own controls. Results: A total of 16 patients were enrolled for a total of 67 weighted blanket sessions. To address safety, no adverse events were observed, the weighted blankets were never removed due to infant distress, and infants experienced no significant temperature change. To address feasibility, 94% of approached mothers were receptive to the use of weighted blankets and staff reported no obstacles to using the blanket. Finally, to assess effectiveness, there was a significant decrease in the infant's heart rate and Finnegan score when a weighted blanket was used. There was no significant change in respiratory rate with the use of a weighted blanket. Implications for Practice: Weighted blankets may be safe, feasible, and effective in decreasing NAS symptoms. Implications for Research: Larger studies are needed to thoroughly study the use of weighted blankets in this population and examine additional outcomes, such as need for pharmacologic intervention, length of hospital stay, and cost of hospital stay.